2017
DOI: 10.1039/c7tc01520h
|View full text |Cite
|
Sign up to set email alerts
|

Red-light emission and dielectric reversible duple opto-electronic switches in a hybrid multifunctional material: (2-methylimidazolium)MnCl3(H2O)

Abstract: A new optical–electrical switching material was synthesized, and it is much superior to the predominant multifunctional devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 34 publications
5
38
0
Order By: Relevance
“…The configuration of the inorganic anionic chains in the HTP remains nearly the same as that in the RTP while the orientation of the organic cations has changed greatly (Table S1). At HTP, the N ‐methylpyrrolidinium cations orientationally disordered over two equivalent positions related by the mirror plane ( m ) (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The configuration of the inorganic anionic chains in the HTP remains nearly the same as that in the RTP while the orientation of the organic cations has changed greatly (Table S1). At HTP, the N ‐methylpyrrolidinium cations orientationally disordered over two equivalent positions related by the mirror plane ( m ) (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…6(b), olive) matches well with the absorption spectra, suggesting that almost all the absorption bands contribute towards the observed emission. 27 The emission is seen to be associated with a single decay process with a long lifetime of 1.71 ms and absolute quantum yield (QY) value of 39.5% (Fig. 6(c)).…”
Section: Photoluminescence Propertiesmentioning
confidence: 96%
“…10 Recently, the red photoluminescent compound (2-methylimidazolium)MnCl 3 (H 2 O) has been reported to display both dielectric and optical switching properties across the order-disorder SPT. 27 Among other Mn-based hybrids, Ren-Gen Xiong et al have recently reported BaNiO 3 -like hexagonal perovskite structures in the compounds TMBMMnBr 3 (Me 3 NCH 2 BrMnBr 3 ) and TMCMMnCl 3 (Me 3 NCH 2 ClMnCl 3 ), both of which exhibit dielectric switching associated with structural phase transitions at high temperature and also very large piezoelectric coefficients. 28,29 The transition temperature (T c ) and thermal hysteresis (DT) are the two major attributes of thermally switchable dielectrics.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure a, DSC curves clearly show two reversible endothermic and exothermic peaks in the heating and cooling runs at 152.4 and 134.5 K, respectively, corresponding to a reversible structural phase transition. The large hysteresis of 17.9 K and the sharp shape of peaks support the presence of a first‐order phase transition . Known from curves, the average entropy change (Δ S ) was estimated to be 1.86 J mol −1 K −1 .…”
Section: Resultsmentioning
confidence: 87%